Marx sobre América Latina, revisión crítica de una enunciación eurocentrada - Güendel, Hermann (2012)
In this essay I review the interpretation of Marx realized from Latin America through the work of Bolivarand the American expropriation of the Mexican California. I propose that this interpretation is not a result of an analysis, but of evaluative prejudgments that, on the base of it´sdiscourse, are constituted by places of enunciation characteristic of the imperial difference.